Contributos e desafios da formação contínua de docentes para a construção da igualdade de género e cidadania - Banha Pomar, Clarinda Jesus; Paiva Balça, Ângela Maria; Santos Magalhães, Olga Maria; Fialho Conde, Antónia (Cuestiones de Género: de la igualdad y la diferencia, 2019)
The prevention and elimination of gender stereotypes and sexism is a problem of priority intervention (European Council, 2018). The educational system, in particular pedagogical practices, play a fundamental role in the construction of the principles of citizenship and gender equality. It is crucial that the continuing teacher training integrate this problem, raising awareness, providing knowledge and developing effective intervention skills. In this article, we intend to describe and to reflect an experience of continuous teacher training that enabled the development of activities and intervention projects in real context of teaching. We will start by presenting the assumptions and the training methodology, then we will describe and critically analyze some of the results of the interventions carried out by the teachers.